Conformational analyses and docking studies of a series of 5-nitrofuran- and 5-nitrothiophen-semicarbazone derivatives in three possible binding sites of trypanothione and glutathione reductases - Vega-Teijido, M.; Caracelli, I; Zukerman-Schpector, J. (Elsevier B.V., 2006)
To explore three possible binding sites of trypanothione and glutathione reductase, namely, the active, the dimer interface and the coenzyme NADPH binding site, a series of eight compounds, nitrofurans and nitrothiophenes derivatives, were docked, using their crystallographic and modeled conformations. Docking results showed that, for both families and both enzymes, compounds are more likely to bind in the interface site, even though there is some probability of binding in the active site. These studies are in agreement with experimental data, which suggest that these class of compounds can act either as uncompetitive or mixed type inhibitors, and also with the finding that there is an alpha-helix which connects the active with the interface site, thus allowing charge transference between them. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: turncoat inhibitors; Chagas' disease; sleeping sickness; docking; Nagana